2002
DOI: 10.1046/j.1528-1157.2002.29301.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of SCN1A Mutations in Familial Febrile Seizures

Abstract: Summary:Purpose: Mutations in the voltage-gated sodium channel subunit gene SCN1A have been associated with febrile seizures (FSs) in autosomal dominant generalized epilepsy with febrile seizures plus (GEFS + ) families and severe myoclonic epilepsy of infancy. The present study assessed the role of SCN1A in familial typical FSs.Methods: FS families were selected throughout a collaborative study of the Italian League Against Epilepsy. For each index case, the entire coding region of SCN1A was screened by denat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…As epilepsy in relatives had the characteristics of idiopathic generalized epilepsy (IGE), the authors concluded that SMEI is genetically linked to FS and to other phenotypes of IGE. The identification of de novo SCN1A mutations in SMEI probands and the lack of SCN1A mutations in families with common forms of IGE (Escayg et al, 2001) or FS (Malacarne et al, 2002) challenged this view and suggested our investigation of the familial antecedents of FS and epilepsy in a homogeneous group of SMEI patients showing SCN1A mutations.…”
Section: Discussionmentioning
confidence: 99%
“…As epilepsy in relatives had the characteristics of idiopathic generalized epilepsy (IGE), the authors concluded that SMEI is genetically linked to FS and to other phenotypes of IGE. The identification of de novo SCN1A mutations in SMEI probands and the lack of SCN1A mutations in families with common forms of IGE (Escayg et al, 2001) or FS (Malacarne et al, 2002) challenged this view and suggested our investigation of the familial antecedents of FS and epilepsy in a homogeneous group of SMEI patients showing SCN1A mutations.…”
Section: Discussionmentioning
confidence: 99%
“…SCN1A mutations were initially found in large families with GEFS+ in 2000 (Escayg, 2000). A missense SCN1A mutation was reported in a family with children who experienced simple febrile convulsions (Mantegazza et al, 2005), but this mutation was considered to be a rare case (Malacarne et al, 2002). There was no comparison of the detection of SCN1A mutations in children under one year of age with FS who did and did not develop Dravet syndrome.…”
Section: Figurementioning
confidence: 99%
“…3 Linkage studies in single rare pedigrees have yielded several mutations in sodium channel subunit genes, [4][5][6] but there is no evidence that these "private" mutations have a role in the causation of common FS. 7 Moreover, the phenotypes in these reported pedigrees are unusual, with many affected members, extended age at onset and offset, and partial seizures and afebrile seizure types sometimes interspersed. 8 This raises further questions about the extent of generalizability of these discoveries for common seizure disorders.…”
mentioning
confidence: 92%